Edukasi Pemanfaatan Moringa Oleifera sebagai Pangan Lokal dalam Pencegahan Anemia Gravidarum pada Ibu Hamil - Dhewi Nurahmawati; Mulazimah; Eko Sri Wulangtyas; Entin Srihadi Yanti; Ardina Rezky Noeraini; Asasih villasari; Aisyah Pradita (Jurnal Dremi (Demi Pengabdi Masyarakat), 2026)
Anemia gravidarum remains a significant health problem among pregnant women and is associated with inadequate knowledge regarding nutritional requirements, particularly iron intake and the utilization of local food sources. This community service activity aimed to improve pregnant women's knowledge about the utilization of Moringa oleifera (moringa leaves) as a nutritional source to support the prevention of anemia during pregnancy. The activity was conducted in Blabak Village, Pesantren District, Kediri City, involving 38 pregnant women. The method consisted of a pre-test to assess participants' knowledge, health education on anemia gravidarum, nutritional requirements during pregnancy, and the nutritional content and benefits of moringa leaves, followed by a post-test. Before the education session, 6 participants (16%) had good knowledge, 18 (47%) had moderate knowledge, and 14 (37%) had poor knowledge. After the education session, the number of participants with good knowledge increased to 32 (84.2%), while 4 participants (10.5%) had moderate knowledge and 2 (5.3%) had poor knowledge. These findings indicate that education on the utilization of Moringa oleifera can improve pregnant women's knowledge and has potential as a promotive and preventive approach based on local food resources to support the prevention of anemia gravidarum. Continuous education is needed to encourage the application of knowledge in daily nutritional practices during pregnancy.